House interior design with Augmented Reality technology - Lam, Yan Shin (2022)
Since Malaysia is becoming more advanced than before, the technology of Augmented Reality (AR) becomes a trend in Malaysia. There are many things that can be shown by using Augmented Reality technology such as the flashcard of letters. The flashcard of letters will become more interesting for the children to read. For example, there will be 3-Dimensional (3D) model to show up and let the children to remember the letters easier. Besides, by using AR technology, it can help people to design their own houses and room. Since if people want to hire an interior designer to design their house and room, the cost will be much higher than using a free AR house interior design application. Thus, to solve this problem, House Interior Design with Augmented Reality (AR) technology is proposed. House Interior Design with Augmented Reality (AR) technology is an application that can help the user to design their own house or room without hiring any interior designer. This application is required the user to scan the given image target to design their room or house. While for the methodology that used in this application is the Rapid Application Development (RAD) model, RAD model consists of 4 phases, which are the requirements planning, user design, rapid construction and cutover. Furthermore, this AR application is developed by using Unity, Vuforia and Microsoft Visual Studio. User Acceptance Test (UAT) will be conducted to test the functionality of the application. 20 respondents will be chosen to test the functionality of the AR application. There are 13 respondents who feel that this AR application is useful for helping them to design their room or house. This AR application is easy to use which the main objective is successfully delivered.